Assessment of age- and sex-dependent changes of cerebellum volume in healthy individuals using magnetic resonance imaging - Baykan, Ali Haydar; Ateşoğlu Karabaş, Sibel; Doğan, Zümrüt; Solgun, Selma; Özcan, Gökhan; Şahin, Şükrü; Erbay, Fatih; Aydın, Ali; Üçkardeş, Fatih; İnan, İbrahim (Journal of Surgery and Medicine, 2019)
Aim: Cerebellum is a structure ingrained in fossa cranii posterior and has a great role in contributing to the coordination of motor functions, regulation of muscle tone, and motor learning, as well as precision and accurate timing. This study primarily aimed to establish a cerebellum measurement scale based on age and sex. Methods: The study was carried out with the approval of Adiyaman Clinical Research Ethics Board and the contributions of Adiyaman University Training and Research Hospital Radiology Department. The data were retrospective cohort study obtained from the magnetic resonance images of 160 individuals (80 female and 80 male). The individuals included in the study were divided into age groups of 0-4, 5-9, 10-19, 20-29, 30-39, 40-49, 50-59 and 60-80 years, each consisting of 10 women and 10 men. All statistical analyses were performed using SPSS program. Results: The cerebellum volume was 139.23 (11.73) cm3 for women and 151.14 (12.30) cm3 for men aged 10-19 years, and the difference was significant (P=0.040). The cerebellum volume of individuals aged 0-4 years was found to be 105.05 (33.28) cm3 with a significant difference compared to the remaining age groups (P<0.001). The total cerebellum volume was calculated as 128.84 (29.66) cm3 for individuals aged 0-17 years and 141.91 (15.06) cm3 for those in the 18-80 years group. It was found to be smaller in the 0-17 age group (P<0.001). Conclusion: Determining the volumes of brain parts in healthy individuals is very important in assessing the aging process, as well as contributing to the differentiation of normal and pathological conditions.